2020
DOI: 10.1021/acs.jmedchem.0c00388
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Development of S6821 and S7958 as Potent TAS2R8 Antagonists

Abstract: In humans, bitter taste is mediated by 25 TAS2Rs. Many compounds, including certain active pharmaceutical ingredients, excipients, and nutraceuticals, impart their bitter taste (or in part) through TAS2R8 activation. However, effective TAS2R8 blockers that can either suppress or reduce the bitterness of these compounds have not been described. We are hereby reporting a series of novel 3-(pyrazol-4-yl) imidazolidine-2,4-diones as potent and selective TAS2R8 antagonists. In human sensory tests, S6821 and S7958, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…The results showed that TAS2R1, 8, and 41 receptors were activated by chloramphenicol [1 mM] 43 , 55 57 ; TAS2R3 and 7 were activated by chloroquine [10 mM] 58 ; TAS2R4 was activated by the Trp-Trp-Trp peptide 59 ; TAS2R5 was activated by 1,10-phenanthroline [1 mM] 60 ; TAS2R9 was activated by procainamide [20 mM] 61 ; TAS2R10 was activated by cucurbitacin E [30 µM] 41 ; TAS2R13 was activated by oxyphenonium [10 mM] 62 ; TAS2R14 was activated by flufenamic acid [0.3 mM] 56 ; TAS2R16 was activated by salicin [10 mM] 63 ; TAS2R38 was activated by PROP [1 mM] 64 ; TAS2R39 was activated by ranitidine [10 mM] 62 , 65 ; TAS2R40 was activated by humulone [30 µM] 66 ; TAS2R43, and TAS2R31 were activated by aristolochic acid [30 µM] 40 ; TAS2R46 was activated by strychnine [300 µM] 41 ; TAS2R30 was activated by denatonium [300 µM] 56 ; TAS2R20 was activated by cromolyn [10 mM] 56 ; and TAS2R50 was activated by andrographolide [1 mM] 67 . In contrast, the negative controls, which the TAS2Rs were replaced by the empty vector, lacked responses to these bitter compounds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that TAS2R1, 8, and 41 receptors were activated by chloramphenicol [1 mM] 43 , 55 57 ; TAS2R3 and 7 were activated by chloroquine [10 mM] 58 ; TAS2R4 was activated by the Trp-Trp-Trp peptide 59 ; TAS2R5 was activated by 1,10-phenanthroline [1 mM] 60 ; TAS2R9 was activated by procainamide [20 mM] 61 ; TAS2R10 was activated by cucurbitacin E [30 µM] 41 ; TAS2R13 was activated by oxyphenonium [10 mM] 62 ; TAS2R14 was activated by flufenamic acid [0.3 mM] 56 ; TAS2R16 was activated by salicin [10 mM] 63 ; TAS2R38 was activated by PROP [1 mM] 64 ; TAS2R39 was activated by ranitidine [10 mM] 62 , 65 ; TAS2R40 was activated by humulone [30 µM] 66 ; TAS2R43, and TAS2R31 were activated by aristolochic acid [30 µM] 40 ; TAS2R46 was activated by strychnine [300 µM] 41 ; TAS2R30 was activated by denatonium [300 µM] 56 ; TAS2R20 was activated by cromolyn [10 mM] 56 ; and TAS2R50 was activated by andrographolide [1 mM] 67 . In contrast, the negative controls, which the TAS2Rs were replaced by the empty vector, lacked responses to these bitter compounds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bitterness may be reduced or blocked at any stage of processing, including in the brain (Coupland and Hayes, 2014; Fotsing et al, 2020; Slack et al, 2010). Sweet taste, for example, is believed to act at least in part by inhibiting bitter signals in the brain (Kroeze and Bartoshuk, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, synthetic TAS2R8 inhibitors that functioned as potent bitter taste blockers have been identified and optimized through using a combination of a stable TAS2R8 cell line for fluorescence-based screening assay and human sensory evaluation 32 . Therefore, our bioluminescence-based assay will serve as a valuable tool as a screening assay to discover TAS2R inhibitors, followed by validation of bitter taste blockers in human test panels.…”
Section: Discussionmentioning
confidence: 99%